ANALYSIS OF OZONE CONCENTRATION CONVERSION PROCESS ON GAS-SENSITIVE SEMICONDUCTOR SENSOR - Tuahman Girsang, Johansen
Tropospheric ozone is a secondary pollutant that can have detrimental effects on humans and the environment when its concentration in ambient air exceeds certain limits. Therefore, monitoring tropospheric ozone concentrations is essential. One alternative method for measuring ozone concentration is through the use of lowcost sensors. In this study, the low-cost sensor employed is the Aeroqual S500, which is based on metal oxide semiconductor technology. The concentration data from the sensor are stored in an internal storage device within the Aeroqual S500. This necessitates periodic data retrieval from the sensor when the storage becomes full. To address this, an alternative approach was implemented utilizing the analog feature of the Aeroqual S500, allowing for remote measurement and data collection via transmission. The results of this study indicate that the performance of the Aeroqual S500 analog system demonstrates good accuracy and precision compared to direct measurements from the Aeroqual S500. The voltage measurements via the Aeroqual S500 analog system show a strong correlation (r = 0.971) with a p-value of 0.000 and a regression coefficient (R² = 0.943) with the ozone concentration values measured by the Aeroqual S500 sensor